Kirigami‐Inspired Deformable 3D Structures Conformable to Curved Biological Surface. Issue 12 (16th October 2018) - Yang, Chao; Zhang, Heng; Liu, Youdi; Yu, Zhongliang; Wei, Xiaoding; Hu, Youfan
Abstract: By introducing stretchability and/or deformability to planar electronics, devices can conformably attach to 3D curved surfaces with minimal invasiveness, which is of great interest for next‐generation wearables in clinical and biological applications. Here, a feasible route is demonstrated to generate deformable 3D structures as a robust platform to construct electronic systems by utilizing silver nanowires/parylene hybrid films in a way analogous to the art of kirigami. The hybrid films exhibit outstanding electrical conductivity along with decent optical transparency, flexibility, and long‐term stability. These merits enable these films to work as electrodes for electrocardiogram recording with comparable accuracy to a commercial counterpart, and to fabricate a 7‐GHz monopole antenna with good omni‐directionality and a peak gain of 1.35 dBi. More importantly, a general scheme for constructing 3D deformable electronic systems is presented, including unique patterning procedures and rational cut designs inspired by kirigami. As an example, deformable transparent humidity sensors are fabricated to work on elbows and finger joints for sweating monitoring. The strategy demonstrated here for 3D deformable system construction is versatile and holds great promise for future advanced health monitoring at diverse and complex epidermal surfaces. Abstract : 3D deformable electronic systems are constructed by utilizing silver nanowires/parylene hybrid films in a way similar to the art of kirigami. This combines unique patterning procedures and rational cut designs, providing a general platform for physiological signal monitoring on curved biological surface. A deformable transparent humidity sensor for sweating monitoring on the elbow and finger joint is demonstrated.